AaeAP2a, a scorpion-derived antimicrobial peptide, combats carbapenem-resistant Acinetobacter baumannii via membrane disruption and triggered metabolic collapse - Luo, Weiyu; Zhang, Liuwei; Gao, Haolei; Li, Huiying; Li, Xiaofeng; Wen, Yuliang; Sun, Huarun; Hang, Bolin; Zhang, Longfei; Zhang, Wei; Liu, Xuehan; Wang, Ruibiao; et al. (Frontiers in Microbiology, 2025)
IntroductionCarbapenem-resistant Acinetobacter baumannii (CRAB) poses a significant global health challenge owing to its high mortality rates and widespread antibiotic resistance. While the clinical utility of last-resort antibiotics, such as colistin, remains limited. Consequently, developing novel antimicrobial agents is imperative. Antimicrobial peptides have emerged as promising candidates against multidrug-resistant pathogens. Animal venom constitutes a rich reservoir of bioactive peptides.MethodsIn this study, in vitro experiments were conducted to assess the antibacterial activity of the scorpion-derived peptide AaeAP2a against CRAB, its inhibition of biofilm formation, as well as its stability and biocompatibility. Additionally, the antibacterial mechanism was investigated, and in vivo efficacy was evaluated using a mouse model of peritonitis-associated sepsis.ResultsAaeAP2a exhibits potent antibacterial activity against CRAB and a significant inhibitory effect on biofilm formation. Moreover, AaeAP2a maintains high stability under a broad range of stressful physicochemical conditions and exhibits promising biocompatibility in vitro. Mechanistically, AaeAP2a disrupts bacterial membrane integrity, increases membrane permeability, reduces the NAD+/NADH ratio, dissipates the proton motive force, decreases ATP production, and induces reactive oxygen species and hydroxyl radical accumulation. Moreover, in a mouse model of peritonitis-associated sepsis, AaeAP2a treatment enhanced survival rates and reduced bacterial burdens in key organs.DiscussionThese findings underscore the potential of AaeAP2a as a promising therapeutic agent for CRAB infections, offering novel strategies for addressing antimicrobial resistance.